Merging and splitting Petri net models within distributed embedded controller design - Gomes, Luís (2014)
Design of distributed embedded controllers can benefit from the adoption of a model-based development attitude, where Petri nets modeling can provide support for a comprehensive specification and documentation of the system together with verification capabilities and automatic deployment into implementation platforms. This chapter presents a Petri nets-based development flow based on composition and decomposition of Petri net models, using Input-Output Place-Transition Petri nets (IOPT nets) as the underlying formalism, allowing reusability of models in new situations through a net addition operation, as well as partitioning of the model into components using a net splitting operation. Distributed embedded controllers are addressed adding the concept of time domains to IOPT nets. Finally, a tool chain framework is presented supporting the whole development process, from specification to implementation, including property verification, simulation, and automatic code generation for deployment into implementation platforms (considering hardware-based implementation and VHDL coding or software-oriented implementation and C coding).